HIV prevalence among female sex workers in Guigang City, Guangxi, China: an 8-year consecutive cross-sectional study - Jingzhen Lai; Chunwei Qin; Eric J. Nehl; Junjun Jiang; Yunxuan Huang; Bingyu Liang; Yuexiang Xu; Jiegang Huang; Zhiliang Xu; Chuanyi Ning; Yanyan Liao; Ning Zang; et al. (BMC, 2018)
Abstract Background Female sex workers (FSW) are a population that are at high risk for HIV infection, and their HIV/AIDS knowledge levels and sexual behaviors are of concern. This study describes changes in HIV prevalence and factors associated among female sex workers in Guigang City, Guangxi, one of the highest HIV prevalence areas in China. Methods Data were derived from an annual cross-sectional venue-based survey, 2008 to 2015, in the form of sentinel surveillance. The participants were recruited using cluster sampling. FSW aged 16 years and above who completed a questionnaire and HIV testing. Both descriptive and multi-level analyses were used to explore factors associated with changes in HIV prevalence. Results Seven thousand four hundred ninety-six FSW were recruited in this study. HIV prevalence among FSW in Guigang City fell into two periods, one with an increasing trend (2008-2011) and one with a decline (2012-2015). Differences between these time periods included age, relationship status, HIV knowledge, consistent condom use, lifetime illicit drug use, history of sexually transmitted infection in the past year, HIV testing, receipt of a condom distribution and education program or HIV counseling and testing, and peer education services. Conclusions Since 2012, a reduction in HIV prevalence among FSW in Guigang City has been observed. The decline of HIV prevalence was associated with coinciding changes in demographic characteristics of FSW, improvement of HIV knowledge and safer sexual behaviors, and a program that promotes condom use, HIV counseling & testing, and peer education.